The equations of motion and energy and the velocity profile of a turbulent boundary layer in a compressible fluid - Young, A. D. (College of Aeronautics, Cranfield, 1951)
As far as the author is aware the derivation of the equations of motion and energy for a turbulent boundary layer in a compressible fluid have not yet been given in detail in any publication. To meet a possible need in this connection this paper puts on record the analysis underlying the equations quoted by the author in Chapter x of the forthcoming Vol. 111 of Modern Developments in Fluid Dynamics.